Investors Preferences On Investment In Returns Basis - et.al, Dr. A. Arunachala rajan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Investors always want to maximize their return on investments. Return may take several forms. Investors expect to receive interest on debentures and dividends on shares. It is essential for the investors to distinguish between realized return and expected return. Realised return means return that was earned or could have been earned. Expected return is the return from an asset that investors anticipate over a future period. So, expected return is a predicted return. It may or may not occur. An investor will be willing to make investment only if the expected return is adequate. But in reality investors do not realise the expected return always. This study is conducted to analyse the returns basis for investor’s preference on investment in Thoothukudi District